2014
DOI: 10.1016/j.jcf.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies to Pseudomonas aeruginosa in cystic fibrosis as a diagnostic tool: A systematic review

Abstract: The detection of serum antibodies to P. aeruginosa shows capacity for early detection of this pathogen and potential utility and viability of incorporation in the diagnostic routine of patients with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 41 publications
0
35
0
12
Order By: Relevance
“…The chronic P. aeruginosa biofilm lung infection leads to a pronounced IgG antibody (15). response against P. aeruginosa components including alginate, and these specific antibodies can be detected in blood and used diagnostically (5,6,(16)(17)(18)(19)(20) (Tables 1-2) (Fig. 3A).…”
Section: Cystic Fibrosis and Biofilm Infection -Pathogenetic And Diagmentioning
confidence: 99%
“…The chronic P. aeruginosa biofilm lung infection leads to a pronounced IgG antibody (15). response against P. aeruginosa components including alginate, and these specific antibodies can be detected in blood and used diagnostically (5,6,(16)(17)(18)(19)(20) (Tables 1-2) (Fig. 3A).…”
Section: Cystic Fibrosis and Biofilm Infection -Pathogenetic And Diagmentioning
confidence: 99%
“…P. aeruginosa serology has proved a useful clinical tool in supporting clinical decision making [15,[17][18][19]. The principle has limitations [20,21], and treatment decisions should not be based on P. aeruginosa antibody levels alone, since the antibody response to some antigens may be delayed [17].…”
Section: Usefulness Of Risk Algorithmmentioning
confidence: 99%
“…Patients with CF are followed closely for their entire lives and there might be a benefit in using serodiagnosis as a complement to routine culture, in the same way that antibodies against Pseudomonas aeruginosa and Aspergillus are used successfully in many CF centres [15][16][17][18][19]. Limitations in the predictive values of such assays have been reported [20], and currently antibody measurements for P. aeruginosa are used clinically in combination with culture results, rather than as stand-alone tests [21].…”
Section: Introductionmentioning
confidence: 99%
“…An example of ancillary methods is the detection of serum antibodies against P . aeruginosa ; however, its use in clinical practice remains controversial [35]. In this study, anti-PaAb showed a positive correlation with sCD40L levels, suggesting that its fluctuation reliably reflects the clinical status of infection by this bacterium.…”
Section: Discussionmentioning
confidence: 63%